2015
DOI: 10.1055/s-0034-1395510
|View full text |Cite
|
Sign up to set email alerts
|

Oral Tadalafil in Children with Pulmonary Arterial Hypertension

Abstract: Oral tadalafil was administered easily and tolerated well and improved mean pulmonary artery pressure (MPAP) in children with PAH, which suggests that oral tadalafil may be more effective and safer than sildenafil in the treatment of PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…This approach has a high sensitivity and specificity for detecting BA, albeit with a low positive predictive value, in keeping with the rarity of the disease. Given the severity and progressive nature of BA, and that both NAC and PDE5 inhibitors are well tolerated in infants (65)(66)(67)(68)(69), combining treatments at this time point may be the most effective strategy, particularly if confirmatory studies can be performed allowing for treatment discontinuation in non-responders and those found not to have BA. Going forward, substitution of PDE5i with activators or stimulators of cGMP might be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has a high sensitivity and specificity for detecting BA, albeit with a low positive predictive value, in keeping with the rarity of the disease. Given the severity and progressive nature of BA, and that both NAC and PDE5 inhibitors are well tolerated in infants (65)(66)(67)(68)(69), combining treatments at this time point may be the most effective strategy, particularly if confirmatory studies can be performed allowing for treatment discontinuation in non-responders and those found not to have BA. Going forward, substitution of PDE5i with activators or stimulators of cGMP might be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the discontinuation rate for tadalafil therapy in children was 6% (30). In a study by Shiva et al conducted on 25 patients aged two months to five years, a significant improvement was seen in MPAP (P < 0.01) (29). They used tadalafil 1 mg/kg daily.…”
Section: Discussionmentioning
confidence: 99%
“…After changing from sildenafil to tadalafil, a significant clinical improvement was seen (P < 0.05). It was also obvious that the use of an oral tadalafil suspension was safe and well-tolerated (29). Unlike sildenafil, the longer halflife of tadalafil makes serum levels more consistent, which may have an advantage with regard to hemodynamics in patients with PAH (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tadalafil has also been evaluated in children with PAH . These open‐label, uncontrolled trials, some of which included patients previously treated with sildenafil, suggested that tadalafil improves hemodynamics and exercise capacity, and is generally well tolerated (Table ). While tadalafil is licensed for use in adults with PAH in Europe and the USA, it is not licensed for use in children in either region.…”
Section: Current Management Of Pediatric Pahmentioning
confidence: 99%